ANALISIS NILAI TAMBAH PENGOLAHAN BIJI KOPI ARABIKA (STUDI KASUS: RUMAH KOPI BANJARSENGON, JEMBER) - Yuli Wibowo; Cita Bella Palupi (Faculty of Agricultural Technology, University of Jember, 2022)
This study aims to analyze the value-added of Arabica coffee beans produced from three coffee processing methods, namely fully washed, honey, and natural. The calculation of value-added uses the Hayami method, while the design of recommendations for increasing value-added uses the ISM method which is integrated with the Pugh method. This research is a case study at the Rumah Kopi Banjarsengon which is one of the coffee processing SMEs in Jember Regency. The results showed that there were differences in the amount of value-added resulting from the use of three different processing methods. The highest value-added was produced in the natural processing of Rp. 10,158/kg (54.40%), followed by fully washed processing of Rp. 9,380/kg (52.58%), and honey processing of Rp. 9,709/kg (52.96%). The results of the value-added analysis can provide guidance for companies to determine production priorities. To increase the value-added in Arabica coffee bean processing, the recommendation of strategies can be done is by controlling production facilities and controlling the quality of the workforce. Keywords: coffee processing methods, green bean coffee, Rumah Kopi Banjarsengon, value-added